1983
DOI: 10.1530/acta.0.1040417
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous remission of cranial diabetes insipidus due to concomitant development of ADH-producing lung cancer – an autopsied case

Abstract: The very rare occurrence of an ADH-producing small cell carcinoma of the lung in a 52 year old male patient with cranial diabetes insipidus since childhood is described. In this case diabetes insipidus disappeared concomitantly with development of lung cancer and re-appeared with shrinkage of the lung tumour by radiation therapy. Further progressive expansion of the primary and metastatic tumours induced the syndrome of inappropriate ADH secretion once again (SIADH). This deterioration in the clinical course w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…ADH‐producing small‐cell carcinoma of the lung has been reported previously [ 11] and radioimmunoassay measurements of urinary arginine vasopressin in patients with bronchial carcinoma were found to be exceedingly high [ 12]. In the present case, numerous immunoreactive cells were found in the tumour after using one of the ADH antisera but not with the others.…”
Section: Discussionsupporting
confidence: 59%
“…ADH‐producing small‐cell carcinoma of the lung has been reported previously [ 11] and radioimmunoassay measurements of urinary arginine vasopressin in patients with bronchial carcinoma were found to be exceedingly high [ 12]. In the present case, numerous immunoreactive cells were found in the tumour after using one of the ADH antisera but not with the others.…”
Section: Discussionsupporting
confidence: 59%
“…Notably, even though we cannot prove that SIADH (syndrome of inappropriate antidiuretic hormone) from bronchogenic carcinoma contributed to the masking of CDI in our patient, it has been reported that paraneoplastic SIADH can paradoxically mask CDI, thereby showing that such diametrically opposing endocrinopathies can co-exist in the same patient and mask the presence of each other. 17 This confl icting and often confusing 'tug-ofwar' hormonal situation challenges the classical diagnostic paradigm and ought to be considered in the list of biologically plausible differentials during the clinical workup of fl uidelectrolyte perturbations in such patients. In patients with pituitary lesions and hypocortisolism, one should therefore be wary of unmasking CDI after instituting glucocorticoid replacement.…”
Section: Discussionmentioning
confidence: 99%